Surgical and Functional Outcome after Endoprosthetic Reconstruction in Patients with Osteosarcoma of the Humerus. Issue 1 (December 2018) - Böhler, Christoph; Brönimann, Stephan; Kaider, Alexandra; Puchner, Stephan; Sigmund, Irene; Windhager, Reinhard; Funovics, Philipp
Abstract Endoprosthetic reconstruction (EPR) is the most widely used reconstruction technique after humeral osteosarcoma (OSA). Complications are common and function is often compromised due to the premise of wide resection. In the current study we evaluated (1) the risk of complications after resection and EPR; (2) the functional outcome and how it is influenced by the preservation/resection of deltoid muscle (DM), rotator cuff (RC), axillary nerve or the type of resection (intra-/extraarticular) and (3) if the preservation/resection of DM, RC, axillary nerve or the type of resection has a negative influence on the oncological outcome. We retrospectively evaluated data of 49 patients with humeral OSA. All patients underwent resection and EPR. Complication-free survival according to the ISOLS classification was estimated by a competing risk model. Functional outcome was evaluated by range of motion (ROM) in abduction and the MSTS score. Eleven patients (22%) had at least one complication. The estimated cumulative incidence for the first complication was 18% at one year, 23% at five years, and 28% at ten years, respectively. Soft tissue failure was the most common complication. ROM and MSTS scores were significantly higher in patients where DM and RC (p = 0.043/p = 0.046) and axillary nerve (p = 0.014/p = 0.021) could be preserved. Preservation of these structures had no negative influence on the surgical margins. In conclusion, EPR is a good treatment method with an acceptable complication rate. Preservation of the abductor mechanism, when possible in the setting of obtaining negative margins, provides superior functional outcome.